2004
DOI: 10.1002/j.1551-8833.2004.tb10682.x
|View full text |Cite
|
Sign up to set email alerts
|

Are we answering the right questions? Improving CCR communication

Abstract: Preliminary studies indicate that Consumer Confidence Reports (CCRs) may not be providing people with the water quality information that they want and can understand. Studies of risk perception and communication suggest that CCRs could be more effective if water suppliers asked their customers about their concerns before issuing a CCR and were allowed to respond to them in the report. The author proposes that rather than continue with the one‐way communication supported by the CCR, utilities should routinely e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Recognizing the need to identify the diverse user groups within the broad category of residential users is only a first step; reaching these different customer segments requires additional resources to develop and target messages appropriate to the various groups. Although recent efforts in broad‐scale public outreach have succeeded in reducing water consumption and conveying water quality messages (Humm Keen et al, 2010; Meyer‐Emerick, 2004), utilities continue to ponder how best to identify specific groups to relay service and other goals on the basis of location and customer‐specific characteristics such as land use, climate, and demographics.…”
Section: Mining Billing Data Helps Highlight Diversity Of Customer Basementioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the need to identify the diverse user groups within the broad category of residential users is only a first step; reaching these different customer segments requires additional resources to develop and target messages appropriate to the various groups. Although recent efforts in broad‐scale public outreach have succeeded in reducing water consumption and conveying water quality messages (Humm Keen et al, 2010; Meyer‐Emerick, 2004), utilities continue to ponder how best to identify specific groups to relay service and other goals on the basis of location and customer‐specific characteristics such as land use, climate, and demographics.…”
Section: Mining Billing Data Helps Highlight Diversity Of Customer Basementioning
confidence: 99%
“…Rather than apply the identical strategies and rate increases to all customers, utilities could benefit from an approach that allows them to target conservation messages and initiatives to the portion of customers with high seasonal discretionary use of water. Even in the absence of mandated customer relationship management, researchers have found that when firms and utilities communicate “good” reasons for their actions, perceptions of price fairness tend to increase (Meyer‐Emerick, 2004; Campbell, 1999). In fact, water suppliers across the United States are piloting new programs to improve the effectiveness of communication and dialogue with customers via customer outreach and public education programs (Harvey & Schaefer, 2009; Shridhar, 1999).…”
Section: Mining Billing Data Helps Highlight Diversity Of Customer Basementioning
confidence: 99%
“…The most commonly reported feedback and misunderstandings about the report were similar to consumer concerns in initial literature about the report. Over half of utilities reported receiving questions or concerns from consumers after reading the report, noted in Johnson (2001), and 38% reported receiving questions about water quality concerns not mentioned, highlighted as a concern by Meyer-Emerick (2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to concerns about the health effects language, participants noted that the CCR could be utilized as an annual report on water quality, including as an opportunity to make consumers more comfortable with their water source (Berberich, 1997). Many authors have since conducted studies with suggestions on how to increase the effectiveness or type of information included in CCRs (Meyer-Emerick, 2004;Phetxumphou et al, 2017;Spiesman et al, 2004). USEPA provides the CCR iWriter tool and reference sheets for utilities to consult when creating their CCR (USEPA, 2009(USEPA, , 2015.…”
Section: Ccr As a Communications Tool Beyond Required Informationmentioning
confidence: 99%
“…Analyses of Water Quality Reports demonstrated that many consumers find them poorly understandable and not responsive to consumers' needs. 137 They are typically written at a 12th grade level instead of the 7−8th grade level recommended for effective communication to the general public. 138 The recent regulatory change to allow Water Quality Reports to be published online with consumers being able to request paper copies 139 should enhance the ability of CWSs to include a color version of the Drinking Water Taste and Odor Wheel 63 as well as use other colored illustrations to present information related to the SMCLs.…”
Section: ■ Information Gaps and Recommendationsmentioning
confidence: 99%